A surface suitable for air water extraction in low temperature environment and its preparation method and application
By using superhydrophobic materials with graded micro-nano structures and solid lubricants in low temperature environments, combined with micron particles with photothermal effect, the problem of icing on the water collection surface at low temperatures is solved, and the water collection efficiency and water safety are improved.
Patent Information
- Application Number
- CN202211685802.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-27
AI Technical Summary
In low temperature environments, the water collection surface of the air is prone to reduce the water collection efficiency due to frost and icing, and existing superhydrophobic materials are difficult to maintain hydrophobicity under low temperature and high humidity conditions, which is prone to ice damage and material damage.
By constructing a graded micro-nano structure blended with micro-particles and adding solid lubricant and photothermal effect micro-particles to the surface of the material, a double defense line is formed to delay the icy droplets and promote frost melting.
Effectively delay the freezing of droplets on low-temperature surfaces, improve water collection efficiency, extend effective air water withdrawal time, and improve water safety and material stability through self-cleaning characteristics and photothermal effects.
Smart Images

Figure CN115818970B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water collection materials and functionalized surfaces, and specifically relates to a surface suitable for collecting water from air in a low-temperature environment, and a preparation method and application thereof. Background Art
[0002] The lack of drinking water is becoming a global challenge, and atmospheric water harvesting devices can help alleviate the shortage of water resources. Atmospheric water harvesting devices are actually "water from the air", which refers to the method of converting moisture in the air into drinking water. This type of device has two working modes: active and passive. Active devices often consume a lot of energy to obtain clean drinking water. If solar refrigeration is used to collect and condense water, the required size of the device can be reduced; passive water harvesting devices do not have energy consumption problems, but mainly rely on weather conditions to collect condensed dew or fog when the humidity is high at night. At present, both methods have received more attention and research, and some devices have been put into use and achieved good results. For example, the "Air-drop" water collector in the desert uses solar power devices for cooling. The adsorption-based atmospheric water collection system usually uses solar energy to create a temperature difference to desorb water and then condense and collect it. The "Water seer" uses wind power to drive the wind wheel to rotate and introduce wind into the pipeline into the underground condenser, and condenses the water in the air through the temperature difference between the ground and underground environments. Regardless of the method used to extract water from the air, the water collection surface is an essential core component, so improving the surface water collection efficiency is particularly important. However, in a low temperature environment, water vapor in the air is easily condensed on an overcooled surface (including the wall of the duct) to produce frost, which not only reduces the water collection efficiency but also makes the water collection process impossible, greatly shortening the effective water collection time.
[0003] Existing research mainly focuses on improving water collection performance in various humidity environments, and rarely considers the frost and freezing phenomenon that may occur in low-temperature environments. Common air water collection includes the process of timely discharge of accumulated droplets or condensed droplets. In low-temperature environments at night and in winter, it is necessary to consider inhibiting the freezing and frosting of condensed water. However, there are relatively few water collection surface materials suitable for low-temperature environments. Water collection in low-temperature environments requires both good hydrophobicity of the surface or material, which can discharge the collected droplets in time to prevent freezing and frosting. At the same time, it is necessary to quickly melt the ice and frost after freezing and frosting so that the surface can be exposed and work normally. Superhydrophobic materials are often used in the field of water collection due to the excellent fluidity of droplets on the surface. Droplets are very likely to bounce and roll off on superhydrophobic surfaces, and they also show great application potential in anti-icing. The larger contact angle of the superhydrophobic surface reduces the contact area between the droplets and the supercooled surface, reducing the heat transfer flux and thus prolonging the freezing time of the droplets. However, since the formation of superhydrophobicity requires the construction of appropriate micro-nano structures on the surface of the material, micron and nano-scale protrusions are conducive to storing air, but they are also susceptible to the invasion of tiny droplets. Therefore, under low temperature and high humidity conditions, the wetting state is easy to change from the Cassel state to the Wenzel state, and superhydrophobic materials are also difficult to avoid ice and frost. In the freezing process, the ice layer is easy to mechanically interlock with the micro-nano structure, causing damage to the micro-nano structure and thus affecting the superhydrophobicity. Inspired by pine needles in nature, solid lubricants are not easy to lose, are resistant to low temperatures, have relatively stable chemical properties, and have a smaller sliding angle than liquid lubricants. It is one of the common raw materials for preparing anti-icing materials, which can make up for the deficiency of superhydrophobic materials that are prone to wetting property changes under low temperature and high humidity conditions to a certain extent. The application of photothermal effect can promote the melting of frost. If the ground air duct in the condensation water collection device is set to a transparent built-in photothermal super-hydrophobic material, the photothermal effect under sunlight can heat the passing wind and increase the temperature difference between the wind above and below the ground. At the same time, at night or in low temperature conditions in winter, it can avoid the formation of condensation water film and ice and frost to a certain extent, thereby improving water collection efficiency and extending the effective air water extraction time.
[0004] References [1] Cheng, S., et al., Photothermal slippery surface showing rapid self-repairing and exceptional anti-icing / deicing property. Chemical Engineering Journal, 2022. 431. After spraying black paint on the polyurethane film, a layer of heated and melted paraffin is applied on the surface. After curing, an anti-icing material with photothermal self-repairing function is obtained. However, since only paraffin is exposed on the surface of the material, the static contact angle of the droplet on its surface is only about 130°, and the droplet is not easy to fall off. References [2] Zhang, H., et al., Solar anti-icing surface with enhanced condensate self-removing atextreme environmental conditions. Proc Natl Acad Sci USA, 2021. 118 (18). An effective self-removal condensate solar anti-icing and anti-frost superhydrophobic surface was prepared by using ultrafast pulsed laser deposition technology to deposit iron oxide and using perfluorododecyltrimethoxysilane as a low surface energy modifier. Although pulsed laser deposition technology has a high deposition rate, produces uniform thin films, and has great development potential, it relies on expensive equipment and a high vacuum and high temperature operating environment. The use of fluorosilanes also inevitably pollutes the environment. Summary of the invention
[0005] In view of the shortcomings of the prior art, in order to avoid ice and frost on the water collection surface in a low-temperature environment, thereby reducing the water collection efficiency of the material, and taking into account the preparation cost and the safety of the collected water, the present invention provides a surface suitable for air water collection in a low-temperature environment, and its preparation method and application. By blending micron particles and nanoparticles to construct a hierarchical micro-nano structure, the super-hydrophobicity of the material can effectively cause the droplets to bounce and roll, or reduce the heat transfer area between the droplets and the low-temperature surface to delay the freezing. Since the super-hydrophobic surface is difficult to resist the phenomenon of frost and ice formation caused by tiny droplets penetrating into the microstructure at low temperatures, and even the accumulated ice layer has a mechanical chain effect on the surface to destroy the micro-nano structure and affect the hydrophobicity, a solid lubricant is added to the coating to construct a second line of defense, so that even if the rough structure of the material surface fails, the liquid flow can quickly shrink and slide on the surface, and the staggered distribution of micron-level flakes is conducive to maintaining hydrophobicity at low temperatures. The addition of particles with photothermal effect can increase the temperature under sunlight exposure, not only can it suppress the surface temperature from dropping below the freezing point at a lower temperature, but also can accelerate the melting of ice when the surface inevitably freezes at extremely low temperatures once the temperature rises slightly, preventing the water collection device from being covered with ice for a long time, reducing the water collection efficiency or even failing to work properly. The self-cleaning properties brought by superhydrophobicity can prevent the accumulation of dirt and the growth of bacteria when the material is used outdoors for a long time, thereby improving the safety of the collected water and the stability of the photothermal performance.
[0006] The purpose of the present invention is achieved by the following technical solutions:
[0007] A method for preparing a surface suitable for air water extraction in a low temperature environment comprises the following steps:
[0008] (1) Nanoparticles and microparticles are hydrophobized separately;
[0009] The nanoparticles and micron particles are mixed with anhydrous ethanol respectively, and ethyl orthosilicate is added after ultrasonic dispersion, and hexamethyldisilazane and deionized water are added after stirring, and after sufficient reaction, they are centrifuged, washed, vacuum dried, and ground for use;
[0010] (2) preparing a hydrophobic coating;
[0011] Adding an organic polymer to an organic solvent, and then adding a solid lubricant thereto, heating the mixture in a water bath to completely melt the mixture, and then adding the hydrophobized nanoparticles and microparticles obtained in step (1), and mixing them evenly to obtain a hydrophobic coating;
[0012] (3) coating and solvent exchange treatment;
[0013] The hydrophobic coating obtained in step (2) is uniformly coated on the substrate; after solvent exchange, the coating is peeled off from the substrate and naturally air-dried to obtain a surface suitable for air water extraction in a low-temperature environment.
[0014] Furthermore, the nanoparticles described in step (1) are one or more of SiO2, TiO2, CdS, WO3, and ZnO nanoparticles, and the particle size of the nanoparticles is 20 to 200 nm; the micron particles are micron particles with photothermal effect (capable of efficiently converting solar radiation energy into thermal energy); the micron particles are one or more of Fe3O4, graphene, and carbon black, and the particle size of the micron particles is 1 to 10 μm.
[0015] Furthermore, the duration of the ultrasonic dispersion in step (1) is 30 to 60 minutes; the time for the sufficient reaction is 10-24 hours; the rotation speed of the centrifugal treatment is 5000 to 6000 r / min, and the duration of the centrifugal treatment is 5 to 7 minutes; the cleaning is anhydrous ethanol cleaning, and the cleaning is performed at least twice; the temperature of the vacuum drying is 80 to 100° C., and the duration of the vacuum drying is 60 to 90 minutes.
[0016] Furthermore, the volume ratio of anhydrous ethanol, tetraethyl orthosilicate, hexamethyldisilazane and deionized water in step (1) is 10:(0.6-0.7):(0.6-0.7):(0.8-1.2); the mass volume ratio of the nanoparticles to anhydrous ethanol is 0.05-0.075:1 g / ml, and the mass volume ratio of the micron particles to anhydrous ethanol is 0.05-0.1:1 g / ml.
[0017] Furthermore, in step (2), the organic polymer is one or both of ethylene propylene diene monomer rubber (EPDM) and polyvinyl butyral (PVB) (the organic polymer serves as a dispersant and a binder); the solid lubricant is one or both of paraffin and beeswax; the melting point of the solid lubricant is higher than 60° C.; and the organic solvent is xylene.
[0018] Furthermore, in the hydrophobic coating in step (2), the mass fraction of the hydrophobic nanoparticles is 5% to 10%, the mass fraction of the hydrophobic micron particles is 12% to 16%, the mass fraction of the organic polymer is 7% to 9%, and the mass fraction of the solid lubricant is 4% to 8%; the temperature of the water bath heating is 90° C. to 100° C.; the mixing is carried out under heating and stirring (to prevent the coating from solidifying during the mixing process and to quickly mix the coating), the heating and stirring temperature is 50 to 70° C., and the heating and stirring time is 1 to 2 hours.
[0019] Furthermore, the coating in step (3) is spin coated or coated using a four-sided coater, the thickness of the coating is 500 μm to 1000 μm, the solvent for the solvent exchange is tert-butyl alcohol, and the duration of the solvent exchange is 2 to 4 hours (the purpose of the solvent exchange is to form micron-sized holes in the hydrophobic coating, and the holes, micron particles and nanoparticles together construct a multi-level micro-nano structure).
[0020] The surface prepared by the above-mentioned preparation method is suitable for air water extraction in a low-temperature environment.
[0021] Furthermore, the surface suitable for air water collection in low-temperature environments has a static water contact angle of greater than or equal to 150° at room temperature, a water rolling angle of less than or equal to 5°; a static contact angle of a 13 microliter water droplet at -20°C is greater than or equal to 110°; and has light response characteristics, and the surface temperature rises by greater than or equal to 18°C when exposed to 1sun of simulated sunlight. It has a high light absorption rate, can be bent and folded arbitrarily, and has good overall flexibility.
[0022] The above-mentioned surface suitable for air water extraction in low temperature environment is used for air water extraction in low temperature environment.
[0023] The surface of the present invention has super hydrophobicity due to the film. At room temperature, the droplets have strong fluidity on the super hydrophobic surface and can bounce and roll down quickly. At low temperatures, due to the presence of micro-nano hierarchical structure and upright thin-sheet paraffin, the surface can maintain good hydrophobicity at low temperatures, so the contact area between the droplets and the surface is small, thereby delaying the freezing function. The surface of the present invention also has good light response characteristics. Under sunlight, the photothermal particles efficiently convert light energy into heat energy. When the heat generated on the surface can offset the low temperature of the environment, it is difficult for the droplets to reach the freezing point on the surface and cannot freeze. When the ambient temperature is extremely low, the surface cannot avoid frost and ice. Once the ambient temperature rises slightly, the presence of the photothermal effect can accelerate the melting of the ice layer. On the other hand, when the bottom ice melts, the addition of multi-level micro-nano structures and solid lubricants forms a double-layer defense line to ensure that the condensed water rolls and slides down in time at low temperatures. Therefore, the repellency of the material to water can make the melted water act as a lubricant, promote the removal of the ice layer and the collection of ice melt water, and reduce ice coverage.
[0024] The surface of the present invention can be applied to water collection systems that need to discharge condensed water in time, prevent ice and frost, and maintain the surface dry and clean. For example, fog collection surfaces that are prone to frost or freezing in low temperature environments. For example, dew collection systems usually require active input of energy to cool the temperature below the dew point, while adsorption-based atmospheric water collection systems usually use solar energy to create a temperature difference to desorb and collect water. Both systems include condensation drainage devices. After the water is condensed, it is necessary to discharge the water in time, and it is necessary to inhibit the condensed water from freezing and frosting on the water collection surface at night and in low temperature environments in winter.
[0025] The material prepared by the present invention can prevent condensed water from forming a film and delay the freezing of droplets in a low-temperature environment through the combined effects of solid lubricants, super-hydrophobic properties and photothermal effects. Under the action of photothermal particles, when droplets inevitably frost and freeze on supercooled surfaces, the melting of frost can be promoted to prevent the device from reducing the water collection efficiency due to icing at low temperatures. The appropriate micro-nanoparticle mass ratio and upright flaky solid lubrication can help the surface maintain good hydrophobic properties at low temperatures. It has good flexibility and can be bent and folded at will, which is convenient and low-cost for use as an important component of a water collector in practical applications to fit with other surfaces of a certain shape. At the same time, super-hydrophobicity gives the material self-cleaning properties, which can further improve the safety of the collected water and the stability of the material's light response.
[0026] The advantages of the present invention are:
[0027] (1) The present invention provides a method for preparing a surface suitable for air water extraction in a low-temperature environment. The preparation process is simple, no expensive equipment investment is required, the cost is low, and it is suitable for large-scale production. In addition, the hydrophobic treatment of nanoparticles and micron particles does not use fluorinated silane to achieve green production.
[0028] (2) The present invention provides a method for preparing a surface suitable for air water extraction in a low-temperature environment. The prepared surface has good flexibility and can be bent and folded arbitrarily, so that it is convenient to fit with other shaped surfaces in practical applications;
[0029] (3) The present invention provides a surface suitable for air water extraction in a low-temperature environment. The self-cleaning property of the material given by the super-hydrophobicity can make the composite material have certain antibacterial properties, thereby preventing the accumulation of dirt and bacteria when the material is used outdoors for a long time. At the same time, the self-cleaning effect makes it easy for dust on the surface to be taken away by water droplets, which ensures the stability of the surface photothermal effect to a certain extent;
[0030] (4) The present invention provides a surface suitable for air water collection in a low-temperature environment, which uses a double line of defense of superhydrophobicity and solid lubrication properties to promote the sliding of liquid water, and combines superhydrophobicity and photothermal properties to intervene in the ice-covering process in a low-temperature environment before and after freezing, so that the water collector can normally collect condensed water or ice melt water at low temperatures;
[0031] (5) The present invention provides a surface suitable for air water extraction in a low-temperature environment, which is based on hydrophobic material modification and morphology control, and has high hydrophobicity and low rolling angle, especially high hydrophobicity retention in a low-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a flow chart of a surface preparation suitable for air water extraction in a low temperature environment provided by the present invention;
[0033] Figure 2This is the folding and bending diagram of the sample in Example 1;
[0034] Figure 3 This is a static contact angle measurement diagram of the sample in Example 1;
[0035] Figure 4a This is a scanning electron microscope image of the sample in Example 1. Figure 4b Comparative Example 2 Sample SEM image, Figure 4c This is a scanning electron microscope image of the sample of comparative example 3;
[0036] Figure 5 The graphs of static contact (CA) of the sample surfaces of Comparative Examples 1-3 and Examples 1-2 versus freezing time;
[0037] Figure 6a The surface temperature variation curve of Example 1;
[0038] Figure 6b A comparison of the surface temperature rise during the light response process of the samples of Example 1 (right) and Comparative Example 1 (left);
[0039] Figure 7a This is a self-cleaning effect diagram of Example 2;
[0040] Figure 7b This is a comparison diagram of the photothermal effect before and after self-cleaning in Example 2;
[0041] Figure 8 This is a diagram of the jet phenomenon of the sample of Example 2 in the air;
[0042] Figure 9a A schematic diagram of a desert water collection device driven by wind turbines or solar energy and utilizing the temperature difference between the ground and underground;
[0043] Figure 9b It is a schematic diagram of a rotatable fin-type double-sided water collection structure. DETAILED DESCRIPTION
[0044] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited thereto.
[0045] Preparation process Figure 1 shown.
[0046] Example 1
[0047] Step 1: Nanoparticles and microparticles are hydrophobized separately;
[0048] 2.5 g of SiO2 nanoparticles with a particle size of 20 nm were mixed with 40 mL of anhydrous ethanol, and 2.8 mL of ethyl orthosilicate was added after ultrasonic dispersion for 15 min. After magnetic stirring for 10 min, 2.8 mL of hexamethyldisilazane was slowly added dropwise. After 30 min, 4 mL of deionized water was added dropwise. After sufficient reaction for 24 h, the mixture was heated at 5500 r·min. -1 The particles were centrifuged at a speed of 1000 nm for 6 min, then washed twice with anhydrous ethanol, dried under vacuum at 85°C for 60 min, and ground in a mortar for later use. 2.5 g of Fe3O4 with a particle size of 1 μm was used as micron particles, and the hydrophobic treatment was the same as that of nanoparticles.
[0049] Step 2: Prepare the hydrophobic coating
[0050] Add 0.875g of ethylene propylene rubber (EPDM3722) to 10mL of xylene, then add 0.5g of paraffin with a melting point of about 60°C, heat in a water bath at 95°C to completely melt the mixture into a colorless, transparent, viscous liquid, then add 1g of nano-SiO2 particles treated with hydrophobicity in step 1 and 1.5g of Fe3O4 micron particles with photothermal effect, heat while stirring at 50°C, stir for 2h, and mix well to obtain the photothermal hydrophobic coating.
[0051] Step 3: coating and solvent exchange treatment;
[0052] The glass substrate was cleaned with ethanol and deionized water in turn, and after air drying, the coating obtained in step 2 was evenly coated on the substrate using a four-sided coater, and the coating thickness was selected to be 750 μm. After the coating was completed, the coating and the substrate were immersed in tert-butyl alcohol. After the solvent exchange for 3 hours, the coating was peeled off from the substrate and naturally air-dried to obtain a super-hydrophobic surface.
[0053] Example 2
[0054] Step 1: Nanoparticles and microparticles are hydrophobized separately;
[0055] 2.5 g of SiO2 nanoparticles with a particle size of 20 nm were mixed with 40 mL of anhydrous ethanol, and 2.8 mL of ethyl orthosilicate was added after ultrasonic dispersion for 25 min. After magnetic stirring for 10 min, 2.8 mL of hexamethyldisilazane was slowly added dropwise. After 30 min, 4 mL of deionized water was added dropwise. After sufficient reaction for 24 h, the mixture was heated at 6000 r·min. -1 The particles were centrifuged at a speed of 5000 nm for 5 min, then washed twice with anhydrous ethanol, dried at 95°C in a vacuum oven for 50 min, and ground in a mortar for later use. 2.5 g of Fe3O4 with a particle size of 1 μm was used as micron particles, and the hydrophobic treatment was the same as that of nanoparticles.
[0056] Step 2: preparing a hydrophobic coating;
[0057] Add 0.875g of ethylene propylene rubber (EPDM3722) to 10mL of xylene, and then add 0.5g of paraffin with a melting point of about 60°C, heat in a water bath at 96°C to completely melt the mixture into a colorless, transparent, viscous liquid, then add 0.6g of nano-SiO2 particles treated with hydrophobicity in step 1 and 1.9g of Fe3O4 micron particles with photothermal effect, heat and stir at 60°C, stir for 1.5h, and mix well to obtain the photothermal hydrophobic coating.
[0058] Step 3: coating and solvent exchange treatment;
[0059] The glass substrate was cleaned with ethanol and deionized water in turn, and after air drying, the coating obtained in step 2 was evenly coated on the substrate using a four-sided coater, and the coating thickness was selected to be 750 μm. After the coating was completed, the coating and the substrate were immersed in tert-butyl alcohol, and after solvent exchange for 2.5 hours, the coating was peeled off from the substrate and naturally air-dried to obtain a super-hydrophobic surface.
[0060] Example 3
[0061] Step 1: Nanoparticles and microparticles are hydrophobized separately;
[0062] 2.5 g of SiO2 nanoparticles with a particle size of 20 nm were mixed with 40 mL of anhydrous ethanol, and 2.8 mL of ethyl orthosilicate was added after ultrasonic dispersion for 25 min. After magnetic stirring for 10 min, 2.8 mL of hexamethyldisilazane was slowly added dropwise. After 30 min, 4 mL of deionized water was added dropwise. After sufficient reaction for 20 h, the mixture was heated at 6000 r·min. -1 The particles were centrifuged at a speed of 5000 nm for 5 min, then washed twice with anhydrous ethanol, dried at 95°C in a vacuum oven for 50 min, and ground in a mortar for later use. 2.5 g of Fe3O4 with a particle size of 1 μm was used as micron particles, and the hydrophobic treatment was the same as that of nanoparticles.
[0063] Step 2: preparing a hydrophobic coating;
[0064] Add 0.875g of ethylene propylene rubber (EPDM3722) and 0.09g of polyvinyl butyral (PVB) to 10mL of xylene, then add 0.6g of paraffin with a melting point of about 60°C, heat in a water bath at 96°C to completely melt the mixture into a colorless, transparent, viscous liquid, then add 0.6g of nano-SiO2 particles treated with hydrophobicity in step 1 and 1.9g of Fe3O4 micron particles with photothermal effect, heat while stirring at 60°C, stir for 2h, and mix well to obtain a photothermal hydrophobic coating.
[0065] Step 3: coating and solvent exchange treatment;
[0066] The glass substrate was cleaned with ethanol and deionized water in turn, and after air drying, the coating obtained in step 2 was evenly coated on the substrate using a four-sided coater, and the coating thickness was selected to be 500 μm. After the coating was completed, the coating and the substrate were immersed in tert-butyl alcohol. After the solvent exchange for 2.5 hours, the coating was peeled off from the substrate and naturally air-dried to obtain a super-hydrophobic surface.
[0067] The water-collecting material suitable for low-temperature environments prepared by the above method has good overall flexibility of the film, such as Figure 2 As shown, it can be bent arbitrarily without deformation. The film shows super hydrophobicity, and the static contact angle of water is greater than 150°. The test results are shown in Figure 3 The scanning electron microscope image of the sample obtained in Example 1 is as follows Figure 4a As shown, since paraffin is insoluble in tert-butyl alcohol, there is a layer of vertical paraffin flakes precipitated on the surface of the material. The material under the paraffin crystals is distributed with irregular holes, and the hole diameter ranges from 1μm to 30μm. The thin flake paraffin precipitated on the surface, the micron-sized holes inside, the micron particles and nanoparticles together construct a multi-level micro-nano structure on the surface. The jet phenomenon of the sample obtained in Example 2 in the air is shown in Figure 8 , water can be effectively bounced off the surface.
[0068] Comparative Example 1
[0069] preparing a hydrophobic coating without photothermal particles;
[0070] Add 0.875g of ethylene propylene diene monomer rubber (EPDM3722) and 0.5g of paraffin wax to 10mL of xylene, heat in a water bath at 95°C for 1h, make the mixture a colorless, transparent, viscous liquid, add 1g of hydrophobic treated silica particles, heat and stir the mixture at 50°C for 2h. Use a four-sided applicator to coat the glass substrate with a coating thickness of 750μm. After coating, perform solvent exchange for 3h, peel the film from the glass substrate and air dry it naturally. The obtained hydrophobic coating has a static contact angle of 152° and a rolling angle of <5°.
[0071] Comparative Example 2
[0072] preparing a paraffin-free hydrophobic coating;
[0073] Add 0.875g of ethylene propylene rubber (EPDM3722) to 10mL of xylene and heat in a water bath at 95°C for 1h to make the mixture a colorless, transparent, viscous liquid. Add 1g of hydrophobic treated silica particles and 1.5g of photothermal particles of ferroferric oxide. Heat and stir the mixture at 50°C for 2h. Use a four-sided applicator to coat the glass substrate with a film thickness of 750μm. After the coating is completed, solvent exchange is performed for 3h, and the film is peeled off from the glass substrate and air-dried naturally. The obtained hydrophobic coating has a static contact angle of 152° and a rolling angle of <5°.
[0074] Comparative Example 3
[0075] The sample obtained in Example 1 was heated at 80° C. for 10 min to obtain a sample of Comparative Example 3.
[0076] The scanning electron microscope image of the sample of comparative example 2 is as follows Figure 4b The surface without paraffin wax is distributed with irregular holes, and a large number of particles are accumulated around the holes. The larger diameter is the iron oxide micron particles, and the smaller diameter is the silicon dioxide nanoparticles with hydrophobic surface treatment directly exposed. Figure 4c It can be seen that the melted paraffin flakes are spread on the surface in the form of blocks, with some hydrophobic particles and pores exposed, while some are covered by paraffin.
[0077] Table 1 Comparison of static contact angles of the embodiments and comparative examples before and after freezing at room temperature and -20°C
[0078]
[0079]
[0080] Table 2 Comparison of ice formation and melting time between the embodiment and the comparative example
[0081]
[0082] Although Examples 1, 2 and Comparative Examples 2, 3 all showed good hydrophobicity at room temperature, and the static contact angles were all greater than 150°, as shown in Table 1, all samples were placed in a low temperature environment of -20°C, water was added to submerge the samples, and the ice layer was melted after freezing for 30 minutes and the samples were taken out of the water. It was found that only the sample surface of Comparative Example 2 without adding paraffin was covered with a thick layer of water film, while the surfaces of other samples still had good water repellency and no liquid film remained. Each sample was frozen at -20°C, the ice layer was melted for a period of time, and the samples were taken out and dried naturally. The static contact angles of each sample were measured to change with time as shown in the following figure. Figure 5The static contact angle in the dry state does not change much, but the droplets on the sample of comparative example 2 without adding paraffin wax are not easy to fall off the surface, and the frozen sample is immersed in water again, and a liquid film is easy to remain. The above experimental results show that the addition of paraffin wax helps to maintain the hydrophobicity of the sample in a low temperature environment.
[0083] From the comparative analysis of the data in Table 1 and Table 2, it can be obtained that, compared with Example 2, Example 1 has a significantly reduced static contact angle on a substrate at -20°C, and a shorter freezing time, which again shows that the addition of paraffin can cause the surface to maintain good hydrophobicity at low temperatures, thereby indirectly extending the freezing time. Compared with Example 1 and Comparative Example 3, the same mass of paraffin was added, but the paraffin in Example 1 was distributed in a staggered manner with upright micron-shaped flakes, while after the sample of Comparative Example 3 was heated, the paraffin melted on the surface of the material and was distributed in a block-like form. The contact angle of Comparative Example 3 is larger at room temperature, but the static contact angle of the surface where the paraffin is distributed in a block-like form is significantly reduced at low temperatures, which shortens the freezing time of the droplets. Therefore, the upright flake-shaped paraffin flakes can enhance the hydrophobic stability of the surface at low temperatures to a certain extent. The mass ratio of micron-sized photothermal particles to nanoparticles in Example 2 is greater than that in Example 1. It is found that the static contact angle of the sample obtained in Example 2 is larger both at room temperature and after ice melting. It can be seen that the appropriate mass ratio of micro-nano particles also helps to improve the stability of the hydrophobic properties of the surface at low temperatures. During the ice melting process, the content of photothermal particles in Example 2 is greater than that in Example 1. Therefore, the ice melting time of the droplets on Example 2 is obviously shortened. In Comparative Example 2, since no paraffin is added, and the thermal resistance of paraffin is large, the heat generated by the photothermal effect in Comparative Example 2 can be transferred to the droplets relatively quickly compared to Example 1, and the ice droplets can melt faster. The composition of paraffin and photothermal particles in Comparative Examples 1 and 3 is consistent, and the melting time of ice droplets is roughly the same.
[0084] The light response experiment of Example 1, Example 2 and Comparative Example 1 was carried out, and a xenon lamp was used to simulate sunlight with a light intensity of 100 mW·cm -2 The samples of Example 1 and Comparative Example 1 were placed under simulated sunlight. After 20 minutes, the xenon lamp was turned off and the surface temperature change was recorded with an infrared camera. Figure 6a and Figure 6bAs shown, it is found that the surface temperature of the sample in Example 1 rises by 18°C within 20 minutes, and the temperature drops rapidly after the simulated sunlight is turned off, showing a good light response characteristic, while the temperature of the sample in Comparative Example 1 has almost no change. When the ice-melting and frost-melting experiments are carried out and the icing experiments with the simulated light turned on, a -10°C semiconductor refrigeration sheet is placed under the sample, the experimental environment temperature is 19°C, and the relative humidity is 57%. The experimental results are shown in Table 2. The water-collecting material suitable for low-temperature environments prepared in the embodiment has a good delayed icing function under simulated sunlight. When the sample is exposed to sunlight in an environment of -10°C, the surface temperature is recorded by an infrared camera. It is found that when the photothermal effect exists, the surface temperature is greater than zero degrees, the droplets cannot reach the freezing point, and the freezing time is infinitely extended. The samples with droplet ice and complete frost are placed under simulated sunlight again. The samples in Examples 1, 2 and Comparative Examples 2, 3 can quickly melt the droplet ice and frost layer, while the comparative examples without adding photothermal particles cannot melt. It can be seen that the material prepared by the present invention has a certain low-temperature environment applicability.
[0085] It is difficult for the water collector to be unaffected by pollutants in actual application. Silica is used to simulate pollutant dust. Figure 7a and Figure 7b The photothermal effect of the display surface will be affected by the pollutants covering the surface, and the heating rate will decrease. However, due to the self-cleaning properties of the super-hydrophobic material, when the water droplets come into contact with the pollutants, they will carry the pollutants with them and roll down. When the pollutants are removed, the photothermal rate will resume again. The self-cleaning properties play a certain role in ensuring the stability of the photothermal effect.
[0086] Based on the properties of the surface prepared by the present invention, it can be applied to the following water collection places but is not limited to the following places. Figure 9a As shown, for a device that uses a wind wheel or solar energy to collect condensed water due to the temperature difference between the ground and the underground, a transparent material is set on the outside of the ground air duct, and the inside is fitted with the surface prepared by the present invention. The temperature of the channel can be increased under sunlight during the day, increasing the temperature difference between the ground and the underground, promoting efficient condensation of the device, and preventing frost or ice from forming on the channel for a long time at night and in low temperature environments in winter. For water intake devices for fog collection and adsorption refrigeration, the fog collection surface and the condensation water collection structure can be set as a rotatable fin-type double-sided water collection structure, such as Figure 9b One side is coated with an efficient water-collecting coating with radiant cooling, and the other side is adhered to the surface provided by the present invention. When the ambient temperature is too low, one side of the photothermal material is utilized to prevent the surface properties of the material from being destroyed or the water-collecting efficiency from being unable to recover for a long time due to frost and ice.
[0087] The above implementation cases are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention are equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a surface suitable for air water extraction in a low temperature environment, characterized in that: The following steps are involved: (1) Nanoparticles and microparticles are hydrophobized separately; The nanoparticles and micron particles are mixed with anhydrous ethanol respectively, and ethyl orthosilicate is added after ultrasonic dispersion, and hexamethyldisilazane and deionized water are added after stirring, and after sufficient reaction, they are centrifuged, washed, vacuum dried, and ground for use; the nanoparticles are SiO2 nanoparticles, and the particle size of the nanoparticles is 20-200nm; the micron particles are micron particles with photothermal effect; the micron particles are Fe3O4, and the particle size of the micron particles is 1-10μm; (2) preparing a hydrophobic coating; The organic polymer is added to the organic solvent, and then the solid lubricant is added thereto, and the mixture is heated in a water bath to completely melt, and then the hydrophobized nanoparticles and micron particles obtained in step (1) are added, and the mixture is mixed uniformly to obtain a hydrophobic coating; the organic polymer is one or two of ethylene propylene diene rubber and polyvinyl butyral ester; the solid lubricant is one or two of paraffin wax and beeswax; the melting point of the solid lubricant is higher than 60°C; the mass fraction of the hydrophobized nanoparticles in the hydrophobic coating is 5% to 10%, the mass fraction of the hydrophobized micron particles is 12% to 16%, the mass fraction of the organic polymer is 7% to 9%, and the mass fraction of the solid lubricant is 4% to 8%; the water bath heating temperature is 90°C to 100°C; the mixing is carried out under heating and stirring, the heating and stirring temperature is 50 to 70°C, and the heating and stirring time is 1 to 2h; (3) coating and solvent exchange treatment; The hydrophobic coating obtained in step (2) is uniformly coated on the substrate; after solvent exchange, the coating is peeled off from the substrate and naturally air-dried to obtain a surface suitable for air water extraction in a low-temperature environment.
2. The method for preparing a surface suitable for air water extraction in a low temperature environment as claimed in claim 1, characterized in that: The duration of the ultrasonic dispersion in step (1) is 30-60 minutes; the time for the full reaction is 10-24 hours; the rotation speed of the centrifugal treatment is 5000-6000 r / min, and the duration of the centrifugal treatment is 5-7 minutes; the cleaning is anhydrous ethanol cleaning; the temperature of the vacuum drying is 80-100°C, and the duration of the vacuum drying is 60-90 minutes.
3. The method for preparing a surface suitable for air water extraction in a low temperature environment as claimed in claim 1, characterized in that: The volume ratio of anhydrous ethanol, tetraethyl orthosilicate, hexamethyldisilazane and deionized water in step (1) is 10:(0.6-0.7):(0.6-0.7):(0.8-1.2); the mass volume ratio of the nanoparticles to anhydrous ethanol is 0.05-0.075:1 g / ml, and the mass volume ratio of the micron particles to anhydrous ethanol is 0.05-0.1:1 g / ml.
4. The method for preparing a surface suitable for air water extraction in a low temperature environment as claimed in claim 1, characterized in that: The organic solvent in step (2) is xylene.
5. The method for preparing a surface suitable for air water extraction in a low temperature environment as claimed in claim 1, characterized in that: The coating in step (3) is performed by spin coating or using a four-sided coating apparatus, the thickness of the coating is 500 μm to 1000 μm, the solvent for the solvent exchange is tert-butyl alcohol, and the duration of the solvent exchange is 2 to 4 hours.
6. A surface suitable for air water extraction in a low temperature environment, prepared by the preparation method according to any one of claims 1 to 5.
7. The surface suitable for air water extraction in a low temperature environment as claimed in claim 6, characterized in that: The surface suitable for air water extraction in a low-temperature environment has a static water contact angle of greater than or equal to 150° at room temperature and a water rolling angle of less than or equal to 5°; a static contact angle of a 13 microliter water droplet at -20°C is greater than or equal to 110°; and has light response characteristics. When exposed to 1 sun of simulated sunlight, the surface temperature rises by greater than or equal to 18°C.
8. Use of the surface suitable for air water extraction in a low-temperature environment as claimed in claim 6 or 7 in air water extraction in a low-temperature environment.
Citation Information
Patent Citations
Micro-nano structure repairing type super-hydrophobic coating and preparation method thereof
CN113652125A